2022
DOI: 10.1021/jacs.2c03454
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment-Sensitive Fluorescent Nucleotide Probes from Benzofuran, Benzothiophene, and Selenophene as Substrates for DNA Polymerases

Abstract: DNA polymerases can process a wide variety of structurally diverse nucleotide substrates, but the molecular basis by which the analogs are processed is not completely understood. Here, we demonstrate the utility of environment-sensitive heterocycle-modified fluorescent nucleotide substrates in probing the incorporation mechanism of DNA polymerases in real time and at the atomic level. The nucleotide analogs containing a selenophene, benzofuran, or benzothiophene moiety at the C5 position of 2′-deoxyuridine are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 96 publications
0
20
0
1
Order By: Relevance
“…The wild type or engineered polymerases that demonstrated activities with unnatural substrates are summarized in Table 3, and the distribution of predominant mutations in the structures of representative engineered unnatural nucleic acid polymerases is illustrated in Figure 4. Although usual modifications of nucleobases, especially those at C5 position of pyrimidines and C7 position of deazapurines, are well tolerated by natural polymerases and broadly used in the labelling and functionalization of DNA and RNA 139,140 , engineering of polymerases can help further increase the enzymatic incorporation efficiency of the nucleotides with base modifications, and even achieve efficient PCR amplification of DNA extensively modified on nucleobases. For example, using CSR method, Holliger and co-workers evolved a mutant of Taq DNAP, M1, that had an expanded substrate spectrum, and could perform efficient PCR amplification of DNAs with 7-deaza-dGTP, FITC-12-dATP, Biotin-16-dUTP or αS-dNTPs replacing corresponding dNTP(s) 79 .…”
Section: Polymerases For the Synthesis Reverse Transcription And Repl...mentioning
confidence: 99%
“…The wild type or engineered polymerases that demonstrated activities with unnatural substrates are summarized in Table 3, and the distribution of predominant mutations in the structures of representative engineered unnatural nucleic acid polymerases is illustrated in Figure 4. Although usual modifications of nucleobases, especially those at C5 position of pyrimidines and C7 position of deazapurines, are well tolerated by natural polymerases and broadly used in the labelling and functionalization of DNA and RNA 139,140 , engineering of polymerases can help further increase the enzymatic incorporation efficiency of the nucleotides with base modifications, and even achieve efficient PCR amplification of DNA extensively modified on nucleobases. For example, using CSR method, Holliger and co-workers evolved a mutant of Taq DNAP, M1, that had an expanded substrate spectrum, and could perform efficient PCR amplification of DNAs with 7-deaza-dGTP, FITC-12-dATP, Biotin-16-dUTP or αS-dNTPs replacing corresponding dNTP(s) 79 .…”
Section: Polymerases For the Synthesis Reverse Transcription And Repl...mentioning
confidence: 99%
“…Our biochemical characterization of templates containing ferrocene analogs of abasic sites revealed that i) canonical nucleotides can be incorporated opposite Fc sites and as for THF-AP sites, the A rule appears to be obeyed; ii) conditions could be met to support the incorporation of less favored pyrimidine nucleotides; iii) polymerases such as Dpo4 do not stall after the installation of a dN-Fc pair and permit bypass synthesis; iv) a two-step protocol method could be envisioned by coupling Dpo4 to other polymerases that stall after the installation of a dN-Fc pair. 21,48,[66][67][68] Since our aim is to use Fc sites to monitor the incorporation of modified nucleotides, we next investigated the compatibility of such ferrocene abasic sites with nucleotides containing different nucleobase modification patterns (Figure 6). First, we evaluated the compatibility of nucleotides that are either characterized by the absence of a base (nucleotide 1) or with an unnatural base surrogate (nucleotide 2) with enzymatic synthesis on templates containing one or multiple Fc sites.…”
Section: Evaluation Of Incorporation Of Modified Nucleotides Opposite...mentioning
confidence: 99%
“…Open Lastly, we evaluated the possibility of incorporating modified dUTP analogs bearing various side-chains and functional groups at position C5 of the pyrimidine which is readily tolerated by numerous polymerases. 10,18,67,70,71,73,74 Therminator, Hemo Klem Taq, and Dpo4 efficiently incorporated the commercially available dU*TP analog 5 opposite an Fc site (Figure S10A), while additional polymerases also appended this nucleotide on primer P1 opposite a THFabasic site (Figure S10B). A slightly lower incorporation efficiency was observed when M1-Sp18 was used as template (Figure S10C).…”
Section: Organic and Biomolecular Chemistry Accepted Manuscriptmentioning
confidence: 99%
“…Lastly, we evaluated the possibility of incorporating modified dUTP analogs bearing various side-chains and functional groups at position C5 of the pyrimidine which is readily tolerated by numerous polymerases. 10,18,65,68,69,71,72 Therminator, Hemo Klem Taq, and Dpo4 efficiently incorporated the commercially available dU*TP analog 5 opposite an Fc site (Figure S10A), while additional polymerases also appended this nucleotide on primer P1 opposite a THFabasic site (Figure S10B). A slightly lower incorporation efficiency was observed when M1-C18 was used as template (Figure S10C).…”
Section: Evaluation Of Incorporation Of Modified Nucleotides Opposite...mentioning
confidence: 99%
“…Our biochemical characterization of templates containing ferrocene analogs of abasic sites revealed that i) canonical nucleotides can be incorporated opposite Fc sites and as for THF-AP sites, the A rule appears to be obeyed; ii) conditions could be met to support the incorporation of less favored pyrimidine nucleotides; iii) polymerases such as Dpo4 do not stall after the installation of a dN-Fc pair and permit bypass synthesis; iv) a two-step protocol method could be envisioned by coupling Dpo4 to other polymerases that stall after the installation of a dN-Fc pair. 21,48,[64][65][66] Since our aim is to use Fc sites to monitor the incorporation of modified nucleotides, we next investigated the compatibility of such ferrocene abasic sites with nucleotides containing different nucleobase modification patterns (Figure 6). First, we evaluated the compatibility of nucleotides that are either characterized by the absence of a base (nucleotide 1) or with an unnatural base surrogate (nucleotide 2) with enzymatic synthesis on templates containing one or multiple Fc sites.…”
Section: Evaluation Of Incorporation Of Modified Nucleotides Opposite...mentioning
confidence: 99%